2017
DOI: 10.2147/ijn.s146516
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in HeLa cancer cells by an ultrasonic-mediated synthesis of curcumin-loaded chitosan–alginate–STPP nanoparticles

Abstract: Natural herbal compounds have been widely introduced as an alternative therapeutic approach in cancer therapy. Despite potent anticancer activity of curcumin, its clinical application has been limited because of low water solubility and resulting poor bioavailability. In this study, we designed a novel ultrasonic-assisted method for the synthesis of curcumin-loaded chitosan–alginate–sodium tripolyphosphate nanoparticles (CS-ALG-STPP NPs). Furthermore, antitumor effect of curcumin-loaded NPs was evaluated in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 42 publications
(1 reference statement)
1
17
0
Order By: Relevance
“…In contrast to our results, some authors have shown that fibroblasts are insensitive to treatment with curcumin. The different findings may be due to the different origins of the studied fibroblasts (neonatal foreskin in [30], fetal lung in [31], and adult skin fibroblasts in our study). Indeed, a number of genes are differentially expressed by epigenetic modifications in the promoter regions.…”
Section: Resultsmentioning
confidence: 84%
“…In contrast to our results, some authors have shown that fibroblasts are insensitive to treatment with curcumin. The different findings may be due to the different origins of the studied fibroblasts (neonatal foreskin in [30], fetal lung in [31], and adult skin fibroblasts in our study). Indeed, a number of genes are differentially expressed by epigenetic modifications in the promoter regions.…”
Section: Resultsmentioning
confidence: 84%
“…The CS, ALG, and STPP solutions have been sonicated to prepare KPF-loaded NPs according to the study of Ahmadi et al [ 25 ]. In brief, 10 ml of 1% acetic acid was used for dissolving 10 mg of CS, and it was stirred via ultrasonic irradiation (Bandelin, Germany) for an hour.…”
Section: Methodsmentioning
confidence: 99%
“…These advantages of alginate and CHI make them promising candidates as nanocarriers for drug delivery [ 37 ]. Various alginate or CHI based nanoparticles have been developed for the delivery of CUR [ 30 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%